2007
DOI: 10.1044/1092-4388(2007/032)
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Utility of Narrative Analysis in Diagnostic Decision Making: Picture-Bound Reference, Elaboration, and Fetal Alcohol Spectrum Disorders

Abstract: Results support further study of the diagnostic utility of narrative analysis using discourse level measures of elaboration and children's strategic use of reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 57 publications
4
57
0
Order By: Relevance
“…It is speculated that the greater occurrence of incomplete utterances in the narration of individuals with FASD may indicate the difficulty that individuals often present in planning and elaboration of the utterances, either in lexical selection or in semantic organization of the words that composed the ongoing utterance as of later statements, which should be related with one another in order to maintain the meaning of the narrative. Syntactic and semantic impairments have been reported in studies investigating the performance of individuals with FASD in language tests (12,15,16,18) or in more naturalistic language samples, such as oral narrative (11,13,14,19) , since individuals with FASD needed revisions and reformulations of utterances throughout the oral narrative.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is speculated that the greater occurrence of incomplete utterances in the narration of individuals with FASD may indicate the difficulty that individuals often present in planning and elaboration of the utterances, either in lexical selection or in semantic organization of the words that composed the ongoing utterance as of later statements, which should be related with one another in order to maintain the meaning of the narrative. Syntactic and semantic impairments have been reported in studies investigating the performance of individuals with FASD in language tests (12,15,16,18) or in more naturalistic language samples, such as oral narrative (11,13,14,19) , since individuals with FASD needed revisions and reformulations of utterances throughout the oral narrative.…”
Section: Discussionmentioning
confidence: 99%
“…As shown, it is noted that, although some studies reported clinical manifestations that signal the difficulties presented by individuals with FASD in oral narrative, as to the microstructural aspects of narrative (13,14,17) and fluency of spoken language (19) , little is known about the aspects that refer to the macrostructural dimension and global coherence of narrative. Also, although the association between the microstructural aspects (referential cohesion) of narrative and the items of the 4-Digit Diagnostic Code (facial characteristics and CNS impairment) has been reported as part of the FASD phenotype (20) , such findings are still to be further explored.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations